NAMA DAN PENAMAAN: PROBLEMATIKA DAN DINAMIKA PERUBAHAN NAMA PADA ORANG JAWA - Sulistiyawan, Andrik (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
Name of the person is an important identity. It could be a medium of identifying a person or certain groups. This article examines the practices of naming and changing names of Javanese person. Some might still consider the practices of changing names as a problem. However, this article aims to question such opinions. In this article I analyze the practices of naming and changing names of the Javanese person from the past to the present. This article is a qualitative research based on literature review. I make use of some secondary sources from the website as well as book and journal collections provided by several libraries in East Java and Yogyakarta. My analysis shows that the name is a dynamic identity. It is confirmed by the change from old Javanese names to Arabic and Islamic names as well as the adoption of Arabic and Islamic names among Javanese person. The dynamics of the names and naming of Javanese people over time is driven by the dynamics of social and political developments.